If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 37 = 90 Reorder the terms: 37 + 2x = 90 Solving 37 + 2x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + 2x = 90 + -37 Combine like terms: 37 + -37 = 0 0 + 2x = 90 + -37 2x = 90 + -37 Combine like terms: 90 + -37 = 53 2x = 53 Divide each side by '2'. x = 26.5 Simplifying x = 26.5
| 17+2x=31-2x | | 12(4+n)+5(-2n-9)=8 | | (5x^2+7x)(20x^2-11x-3)=0 | | 2a+1=148 | | 12(4+n)+5(-2-9)=8 | | 9xy-6yx+x-2y= | | 17x-13y=11 | | .5x+7=6 | | 180-3x=42x+20 | | 21x-3=-63 | | -2-5x=10x-8 | | 2x^2-24x-64=0 | | -159-(-172)= | | 3f-12=-f-15 | | y+3=10x | | 6x-4y-11y+7x+9= | | (2x^2-1)(4)-(x+1)(4)=0 | | 3a(4a-7)= | | 36-3y=-9 | | -(2x-1)-3x=-3(x+4) | | y-3=8x | | 2y^2=4y-1 | | -4+9x-4= | | 3x^2+7x+1=0 | | 3x+42-5x=2-6x+4 | | -4+9-4= | | y-8=3x | | 0=-4.9t^2+80t | | 6-7n=88 | | 9x-7=5x-2x+3 | | -9x-7=5(2x)+3 | | 4x(6-7)=36 |